Enormous Valley Splitting in Monolayer WS2 by Coupling with an N‐Terminated GaN Substrate. Issue 4 (1st February 2021) - Wu, Zhiming; Zeng, Hao; Tang, Weiqing; Ke, Congming; Wu, Yaping; Li, Xu; Kang, Junyong
Abstract : Valleytronics offers another degree of freedom associated with the valley, which is promising for future applications in information processing and storage. Herein, a novel strategy is proposed for generating enormous valley splitting in monolayer WS2 by coupling with an N‐terminated GaN substrate based on first‐principles calculations. The results suggest that N‐terminated GaN is ferromagnetic, inducing considerable valley splitting (251.2 meV) in WS2 . This valley splitting is attributed to the combination of the Zeeman effect and valley state hybridization in the top valence band between WS2 and the GaN substrate. Based on the k · p model, the Zeeman magnetic field of 116 T and the equivalent magnetic field generated by the hybridization of ≈1.68 × 10 3 T are estimated. Furthermore, the strength of the spin‐valley polarization can be modified by tuning the interlayer distance and the in‐plane strain. The valley splitting increases from 251.2 to 426.3 meV when the interlayer distance is decreased from 2.52 to 2.30 Å. The value reaches 353.2 meV for the compressive strain of −3%. New vistas are opened for valley splitting by weak magnetic substrates. Abstract : A considerable valley splitting of 251.2 meV in WS2 is induced by ferromagnetic N‐terminated GaN. Furthermore, the splitting strength can be modified by tuning the interlayer distance or the in‐plane strain.